Fabrication and Characterization of P3HT:MR:PCBM Blend Based Organic Phototransistor - Tauqeer, T.; Yasin, Muhammad; San, Sait E.; Rahman, Hamood Ur; Karimov, Kh. S. (Amer Scientific Publishers, 2017)
Results of an organic phototransistor, fabricated using the blend of poly(3-hexylthiophene) (P3HT), Methyl Red (MR) and [6,6]-phenyl C61-butyric acid methylester (PCBM) are presented in this investigation. Device was processed in MESFET configuration with top gate and bottom drain source contacts. Physical Vapour Deposition technique was used to make Drain, Source and Gate contacts. AFM and UV-Vis absorption spectroscopic techniques were used to study the structural and optical properties of semiconducting layer, respectively. Measurements of the device were taken under dark as well UV-Vis illuminations. Results showed that the device has followed the behaviour of a typical p-type low voltage photo Organic Field Effect Transistor (photo-OFET). Further, device has demonstrated weak saturation trend with low gate leakage current. Photo sensitivity and responsivity values of the device were found to be equal to 27 and 0.3 mA/W, respectively, at V-GS = -3 V, V-DS = -5 V under an illumination intensity of 100 mW/cm(2).
Keywords: P3HT; Methyl Red; PCBM; UV-Vis Illumination; MESFET; Phototransistor